Free testing for BReast CAncer (BRCA1/2) gene mutations in Goiás: Distribution of specialist doctors (Research, Society and Development, 2026)
Objective: This study aimed to assess the number of medical oncologists, mastologists, and geneticists registered with the Regional Medical Council of the State of Goiás (CREMEGO). Methods: This study was conducted in August 2025 as a cross-sectional, quantitative investigation using the public CREMEGO database. Active and inactive registrations of oncologists, mastologists, geneticists, and platform variations were included. Data were tabulated in Excel and analyzed using descriptive statistics. Results: A total of 285 registrations were identified, with 81.4% of them being active. Among active registrations, mastologists accounted for 33.7%, and clinical oncologists accounted for 32.3%. Geneticists were poorly represented (n = 08). A concentration of professionals was observed in Goiânia, with 69.4% of active registrations located in the capital, reaching 100% in some subspecialties. Conclusion: The records indicate that specialists exist in Goiás, but they are centralized in the capital, creating access barriers to genetic testing and counseling for municipalities in the interior and potentially hindering the full implementation of Law Number (No.) 20.707. We propose expanding specialist training in genetic counseling, promoting telemedicine, and decentralizing services to reduce health disparities and inequalities.